AUTHENTICATION DEVICE AND AUTHENTICATION SYSTEM - FUKUI YUICHI (2021)
To provide an authentication device and an authentication system which can perform authentication without individually registering authentication information in a facility which is not connected to a network, and can unitarily manage the facility.SOLUTION: A portable authentication device 3 includes: a wireless reception unit 35 which wirelessly receives identification information on a facility; a reception unit 31 which receives accessible information, for each user's facility, about whether or not the facility is accessible; a storage unit 33 which stores the accessible information received by the reception unit 31; and a control unit 37 which determines accessibility to the facility of the identification information wirelessly received by the wireless reception unit 35, based on the accessible information stored in the storage unit 33.SELECTED DRAWING: Figure 2 【課題】ネットワークに接続されていない設備において個別に認証情報を登録することなく認証を行うことができ、設備を一元管理することができる認証装置及び認証システムを提供する。【解決手段】持ち運び可能な認証装置３は、設備の識別情報を無線受信する無線受信部３５と、ユーザの設備毎のアクセス可能か否かに関するアクセス可能情報を受信する受信部３１と、受信部３１により受信したアクセス可能情報を記憶する記憶部３３と、記憶部３３に記憶されているアクセス可能情報に基づいて、無線受信部３５により無線受信した識別情報の設備へのアクセスの可否を判定する制御部３７と、を有する。【選択図】図２